Inverse relationship between plasminogen activator inhibitor-1 activity and adiponectin in overweight and obese women - Mertens, Ilse; Ballaux, Dominique; Funahashi, Tohru; Matsuzawa, Yuji; Planken, Marc Van der; Verrijken, An; Ruige, Johannes B.; Van Gaal, Luc F. (Thrombosis and Haemostasis, 2005)
Adipose tissue is an active endocrine organ secreting different adipokines such as plasminogen activator inhibitor-1 (PAI-1) and adiponectin, among many others. In this study, we investigated the association between PAI-1 activity and serum adiponectin levels in a group of 444 overweight and obese women and assessed the interrelationship with visceral adipose tissue (VAT; CT-scan L4-L5), insulin resistance (HOMA-IR), HDL cholesterol (HDL-chol) and inflammation (hs-CRP). PAI-1 was inversely related to adiponectin (r=-0.25, p<0.001; adjusted for age and BMI).After adjustment for age, VAT, HOMA-IR and hs-CRP, the relationship remained significant (r=-0.15; p=0.001), but disappeared after additional adjustment for HDL-chol (r=-0.09; p=0.067). Subjects were divided in two groups according to the median levels of adiponectin or PAI-1 levels. PAI-1 activity (19.1±11.4 vs. 15.8±8.6 AU/ml; p=0.003) and adiponectin levels (9.8±4.6 vs. 8.4±4.0 μg/ml; p<0.001) were significantly higher in the low adiponectin/PAI-1 groups. The difference in PAI-1 remained significant after adjustment for age and BMI (p=0.001), became borderline significant after adjustment for age and VAT (p=0.052), and disappeared after adjustment for age and HOMA-IR (p=0.116) or age and HDL-chol (p=0.443).The difference in adiponectin levels remained significant after adjustment for age, VAT, HOMA-IR and hs-CRP (p=0.006), but disappeared after additional adjustment for HDL-chol (p=0.089). Further analyses suggest a contribution of HOMA-IR and/or HDL-chol in the relationship between PAI-1 and adiponectin. HDL-chol was found to be the only factor independently determining both factors. In conclusion, in overweight and obese women, PAI-1 activity was inversely related to serum adiponectin, independent of visceral adipose tissue.
Keywords: Adiponectin; HDL cholesterol; insulin resistance; plasminogen activator inhibitor-1; subclinical inflammation; visceral adipose tissue